Macroeconomic Determinants of Indonesian Tourism Demand in Malaysia - Ahmad Feri, Tanjung; Fung, Thai Thien; Puah, Chin Hong; Brahmana, Rayenda Khresna; Ronald Hasudungan, Sianturi (American Scientific Publishers, 2017)
Indonesia is Malaysia’s second tourist generating country after Singapore, therefore it is important to look at the macroeconomic determinants of Indonesia tourism demand in Malaysia in order to maintain and sustain the significant Indonesian tourist inflows into Malaysia. This study employed quarterly data from 2000Q1 to 2014Q4 to estimate Indonesian tourism demand with the explanatory variables of real income, travel cost and exchange rate. The empirical findings suggest that there is a long-run equilibrium relationship between Indonesian tourism demand and the specified determinants. In summary, higher Indonesian real income, higher travel cost and stronger Indonesian currency will encourage more Indonesian visitors visiting Malaysia.